Survei Tingkat Kebugaran Jasmani Siswa Kelas X SMKN 1 Singosari melalui Tes Kekuatan : Push-Up, Sit-Up, dan Back-Up - Hernanda, Yefta; Arumdalu, Zenithia Salmaa; Isnaini, Lalu Moh Yudha (Universitas Hamzanwadi, 2025)
The purpose of this study was to determine the level of physical fitness of class X students of SMKN 1 Singosari. This research method uses a descriptive quantitative approach. The population in this study was class X students of SMKN 1, namely 799 Singosari students. The sample size was 103 students. Data were collected through direct observation with TKJI measurements. The data analysis technique was carried out by calculating the average score of each type of test and comparing it with the TKJI national assessment category. male students showed 12 students in the very good category, 20 students in the good category, 11 students in the sufficient category, 6 students in the less category, and 1 student in the very less category. While female students showed 8 students in the excellent category, 31 students in the good category, 10 students in the sufficient category, 3 students in the less category, and 1 student in the very less category. These results indicate that 20 19% of students are in the excellent category. The results of the analysis showed that the majority of students had muscle strength in the “good” and “fair” categories, with the back-up test providing the best results. These findings suggest that students use their lower back muscles more than their arms and abdominals. In addition, male students are usually better than female students.